2011
DOI: 10.4028/www.scientific.net/amr.374-377.1230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fly Ash and Slag Powder on Coefficient of Thermal Expansion of Concrete

Abstract: In order to study the effect of fly ash (FA) and slag powder (SP) on coefficient of thermal expansion (CTE) of concrete, the influence of FA and SP to CTE of concrete was compared, the influence of replacement proportion of FA to CTE of concrete was tested, and the unhydrate mineral admixture particles were observed with SEM and validate with Energy Spectrometry. The results showed that the influence of FA and SP to CTE of concrete is different, the CTE of SP concrete is near to the norm concrete,but is higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The measurement results in Table 5 show that the thermal expansion coefficient initially increases and then decreases with the increase of MEA doping rate. According to the research conducted by Gui Bo Gao [ 40 ] and other teams, it is known that the coefficient of thermal expansion is related to the density of the material, and materials with a compact and dense structure tend to have higher coefficients of thermal expansion. In mixtures with lower initial content, the delayed hydration property of MgO contributes to filling the cracks in the cement particles, resulting in a denser cement structure and improving the coefficient of thermal expansion to some extent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement results in Table 5 show that the thermal expansion coefficient initially increases and then decreases with the increase of MEA doping rate. According to the research conducted by Gui Bo Gao [ 40 ] and other teams, it is known that the coefficient of thermal expansion is related to the density of the material, and materials with a compact and dense structure tend to have higher coefficients of thermal expansion. In mixtures with lower initial content, the delayed hydration property of MgO contributes to filling the cracks in the cement particles, resulting in a denser cement structure and improving the coefficient of thermal expansion to some extent.…”
Section: Resultsmentioning
confidence: 99%
“…The measurement results in Table 5 show that the thermal expansion coefficient initially increases and then decreases with the increase of MEA doping rate.. According to the research conducted by Gui Bo Gao [40] and other teams, it is known that the coefficient of thermal…”
Section: Effect Of Mea On the Expansion Coefficient Of Concretementioning
confidence: 96%
“…On the other hand, when increasing the porosity in the paste containing fly ash and slag, they observed reduced CTE of the paste, while increasing porosity in the paste containing silica fume increased the CTE. Moreover, Gao et al [28] added fly ash to concrete and concluded that it caused a significant decline in CTE. However, the addition of the slag resulted in growth at an early age.…”
Section: Introductionmentioning
confidence: 99%